Polygraph Testing in the Courtroom: Legal and Ethical Challenges in Southeast Asia - Manuel, Erwin Miguel; Badar Jr., Dominador (International Journal of Sustainability and Advanced Integrated Research, 2026)
This review offers a thorough examination of the scientific, legal, and ethical aspects of polygraph testing, focusing on the evolving judicial landscape in Southeast Asia from 2016 to 2026. Polygraphy remains a controversial tool in global criminal justice systems, with its widespread use in investigations often contrasted by significant skepticism regarding its scientific and legal validity. While some studies of the Comparison Question Test suggest that it offers a meaningful improvement over traditional methods of detecting deception, the scientific community still raises concerns about its validity and the high risk of false positives. The research reveals considerable variation in legal standards across the region, with countries like Indonesia treating polygraph results as a novel issue in criminal evidence, while Singapore maintains a strict policy of rejecting polygraph results in court. The review also explores how the move toward digital and AI-driven justice systems in nations such as Malaysia and Singapore raises concerns about algorithmic bias and the transparency of decision-making processes. Of particular importance is the constitutional impact of polygraph testing, including issues related to the right against self-incrimination and the emerging concept of "brain privacy." By synthesizing insights from various fields, this study supports the United Nations Sustainable Development Goal 16, which focuses on promoting peace, justice, and strong institutions. It advocates for the creation of unified, evidence-based forensic standards that protect judicial integrity. The paper concludes with a policy framework that calls for region-specific research and the development of ethical guidelines to ensure that advancements in forensic technologies do not infringe upon fundamental human rights.